HUBUNGANTINGKAT PENGETAHUAN DAN SIKAP MASYARAKAT DENGAN TINDAKANPEMBERANTASAN NYAMUK 3M-PLUS - Berot, Fransiskus Hardin (Menara Ilmu, 2018)
Dengue Hemorrhagic Fever (DHF) is a disease caused by Dengue virus. Accordingto data obtained each year, the incidence of DHF has increased and there are still manypeople or families who suffer from DHF. This happens due to lack of knowledge andattitude of the community in the implementation of PSN 3M Plus. This study aims todetermine the relationship Between Knowledge Level and Community Attitudes with 3MPlus Action in the Working Area Puskesmas Belimbing Padang City Year 2017. The typeof research used is an analytical survey with cross sectional study approach. The studywas conducted on Desember 5 to December 18, 2017. The number of samples from thisstudy is 100 heads of households. Multistage Random Sampling. Data collection was doneby interview, observation and questionnaire. Data analysis technique with univariate andbivariate analysis. Data is processed by computerized by Chi-Square test. Based on theresults of this study, 63.0% have a high knowledge, 59.0% have a positive attitude, and58.0% doing 3M plus PSN action. From bivariate test result there is no correlationbetween knowledge with action of PSN 3M Plus (p value = 0,987). And there is an attituderelationship with PSN 3M Plus (p value = 0,030). This research is expected for officers atPuskesmas Belimbing Padang City to further intensify information disseminationintensively to the community about the importance of doing PSN 3M Plus activities toprevent the happening of DHF.Keywords : Knowledge, Attitude, PSN Action 3M Plus